Deposits, Loans, and Banking: Clarifying the Debate. (1st July 2013) - Bagus, Philipp; Howden, David; Block, Walter
Abstract The relationship between banking deposits and loans is contentious. While the defense of a 100 percent reserve clause to eliminate fractional reserves has commonly been asserted on economic and ethical grounds, Huerta de Soto (2006) arguments are largely ignored. Rozeff (2010) is an example. We show that treating a loan and a deposit interchangeably is impermissible due to both established and a priori legal principles. At best, fractional reserves may be considered an aleatory contract but this is incompatible with the reason individuals hold money—mitigating uncertainty. Deposit and loan contracts are distinct, and may not be contractually melded together.